2023
DOI: 10.1097/hep.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Pathway to global elimination of hepatitis B: HBV cure is just the first step

Abstract: Hepatitis B (HBV) is a major cause of global morbidity and mortality, and the leading cause of liver cancer worldwide. Significant advances have recently been made toward the development of a finite HBV treatment that achieves permanent loss of HBsAg and HBV DNA (so-called “HBV cure”), which could provide the means to eliminate HBV as a public health threat. However, the HBV cure is just one step toward achieving WHO HBV elimination targets by 2030, and much work must be done now to prepare for the successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…1 Upon infecting the liver cells of the host, HBV not only generates covalently closed circular DNA (cccDNA) within the cells' nuclei but also integrates its double-stranded linear DNA (dslDNA) into the human genome. 2 The presence of integrated HBV contributes to the instability of the chromosomal structure in patients and allows for the transcription and translation of viral proteins, including HBsAg and truncated HBx. 3,4 Research has demonstrated that integration is the primary contributor to the presence of HBsAg in chronic hepatitis B (CHB) patients with HBeAg negative and low HBV load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Upon infecting the liver cells of the host, HBV not only generates covalently closed circular DNA (cccDNA) within the cells' nuclei but also integrates its double-stranded linear DNA (dslDNA) into the human genome. 2 The presence of integrated HBV contributes to the instability of the chromosomal structure in patients and allows for the transcription and translation of viral proteins, including HBsAg and truncated HBx. 3,4 Research has demonstrated that integration is the primary contributor to the presence of HBsAg in chronic hepatitis B (CHB) patients with HBeAg negative and low HBV load.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, approximately 296 million individuals suffered from chronic HBV infection in 2019, resulting in over 820 000 deaths 1 . Upon infecting the liver cells of the host, HBV not only generates covalently closed circular DNA (cccDNA) within the cells' nuclei but also integrates its double‐stranded linear DNA (dslDNA) into the human genome 2 . The presence of integrated HBV contributes to the instability of the chromosomal structure in patients and allows for the transcription and translation of viral proteins, including HBsAg and truncated HBx 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…HBV transmission occurs through various routes, primarily via perinatal transmission, unsafe medical procedures, and unprotected sexual contact [ 16 ]. The chronicity of the infection varies geographically, with a significant proportion of infected individuals progressing to CHB infection, a long-term condition carrying substantial morbidity and mortality risks [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, children with chronic hepatitis B (CHB) require active antiviral therapy to delay the disease progression and minimize the risk of long-term adverse outcomes [ 6 ]. The optimum result of antiviral therapy for CHB is commonly considered a functional cure, marked by the absence of HBsAg and undetectable HBV-DNA in the serum, with or without the seroconversion of hepatitis B surface antibodies (HBsAb) [ 7 ]. The pursuit of a functional cure should be given high priority for certain select patients.…”
Section: Introductionmentioning
confidence: 99%